A Review of Factors Affecting the Mechanical Performance of PLA in FDM 3D Printing - Saefudin, Slamet; Samsudi Raharjo; Ilham Yustar Afif; Syarifudin; Purnomo; Muhammad Omar Rusydi; Kuzmin Anton; Muhammad Subri; M. Edi Pujianto (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
3D printing has rapidly evolved due to its significant advantages in rapid prototyping. 3D-printed products for industrial applications require stable mechanical properties, which are influenced by various factors. The lack of a comprehensive discussion addressing the factors affecting mechanical properties is the main reason for this review. This article aims to provide an overview of Fused Deposition Modeling (FDM) 3D printing concerning the factors that influence the mechanical performance of FDM 3D products using polylactic acid (PLA) material. The article covers the impact of material factors, process parameters (such as layer thickness, infill patterns, print orientation, infill patterns, infill density, infill width, temperature, and printing speed), as well as post-processing treatments as key considerations. The contribution of this article is to explain to researchers and industry practitioners the factors that affect the mechanical performance of FDM 3D printed products.